Cabozantinib Eradicates Advanced Murine Prostate Cancer by Activating Antitumor Innate Immunity - Patnaik, Akash; Swanson, Kenneth D.; Csizmadia, Eva; Solanki, Aniruddh; Landon-Brace, Natalie; Gehring, Marina P.; Helenius, Katja; Olson, Brian M.; Pyzer, Athalia R.; Wang, Lily C.; Elemento, Olivier; Novak, Jesse; et al. (Cancer discovery, 2017)
Several kinase inhibitors that target aberrant signaling pathways in tumor cells have been deployed in cancer therapy. However, their impact on the tumor immune microenvironment remains poorly understood. The tyrosine kinase inhibitor cabozantinib showed striking responses in cancer clinical trial patients across several malignancies. Here, we show that cabozantinib rapidly eradicates invasive, poorly differentiated PTEN/p53-deficient murine prostate cancer. This was associated with enhanced release of neutrophil chemotactic factors from tumor cells, including CXCL12 and HMGB1, resulting in robust infiltration of neutrophils into the tumor. Critically, cabozantinib-induced tumor clearance in mice was abolished by antibody-mediated granulocyte depletion or HMGB1 neutralization or blockade of neutrophil chemotaxis with the CXCR4 inhibitor plerixafor. Collectively, these data demonstrate that cabozantinib triggers a neutrophil-mediated anticancer innate immune response, resulting in tumor clearance. Significance: This study is the first to demonstrate that a tyrosine kinase inhibitor can activate neutrophil-mediated antitumor innate immunity, resulting in invasive cancer clearance. Cancer Discov; 7(7); 750–65. ©2017 AACR. This article is highlighted in the In This Issue feature, p. 653